The Influence of Management Information Technology and Intellectual Intelligence on Employee Work Productivity PT. Perintis Perkasa Medan - Imanuel Tarigan; A. Mahendra; Dedik Wiryawan; Farid Ardyansyah; Hendrik (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of management information technology and intellectual intelligence on the work productivity of employees of PT. Perintis Perkasa Medan. The decline in employee work productivity is due to management information technology and intellectual intelligence. The population in this study was: 128 employees. The number of samples in this study was 97 employees. The sampling technique used is simple random sampling. Data collection techniques are by distributing questionnaires, interviews, and documentation studies. Data analysis uses multiple linear regression analysis. The study concludes that Partially Information Management Technology has a positive and significant effect on the Employee Productivity of PT. Perintis Perkasa Medan. Partially, Intellectual Intelligence has a positive and significant effect on the Employee Productivity of PT. Perintis Perkasa Medan. Simultaneously Management Information Technology and Intellectual Intelligence have a positive and significant effect on the Employee Productivity of PT. Perintis Perkasa Medan.